Dissecting the Differences between Crown Witnesses and Justice Collaborators - Munawar, Kukun Abdul Syakur; Vitalia, Filda (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: This paper thoroughly examines the conceptual and legal distinctions between crown witnesses and justice collaborators within the Indonesian criminal law framework, as well as their ramifications for the concepts of fair trial and the human rights of defendants.Purposes of the Research: This paper aims to thoroughly analyze the legal status, normative foundation, and implications of using these two groups of witnesses within the framework of procedural justice for defendants.Methods of the Research: This research employs normative legal methodologies, utilizing an analytical approach to positive law, Supreme Court jurisprudence, and relevant human rights concepts.Findings of the Research: The research indicates that the crown witness, stemming from prosecution case-splitting, often violates the principle of non-self-incrimination and undermines the rights of the accused. Conversely, justice collaborators, governed by Supreme Court Circular Letter Number 4 of 2011, adhere to due process of law by voluntary collaboration and a precise legislative framework. The study's novelty is in its comparative analysis that distinctly differentiates these two often-confused processes by including doctrinal interpretation and human rights views. This study addresses a deficiency in previous research, which has seldom investigated their normative convergence, and advocates for a more cohesive, rights-based framework for managing offenders within Indonesia's criminal justice system.